Comparison Of PLC Based Servo Pneumatic System Performance Using PID Controller - Ooi, Choon Kiat (UTeM, 2017)
In this study. the performance of a servo pneumatic system is realized and compared by using the proportional-integral-derivative (PI D) controllers of two different programmable logic controllers (PLC) experimentally. Different PLCs may have different built-in PID controllers and their performance may different during applications. Omron and Siemens have been used for experimentation. For the servo pneumatic system, instead of pneumatic proportional servo valve, on/off solenoid valves are used to control the pneumatic actuators by applying pulse width modulation (PWM) scheme. The positioning voltage is employed as feedback voltage for the PID controller which is used to compare with reference set value for error value generation. Error minimization is greatly depends on the performance of the PID controller. Experimentally, the feedback positioning voltages are captured and plotted as tracking performance. From the tracking perfonnance plots analyses, the performances of the servo pneumatic system are detennined for both PLCs. The experiments results shows that Siemens PLC is better performed than Omron PLC in terms of performane.